THE DISCOURSE OF POWER/THE POWER OF DISCOURSE - Munejah Khan (Proverbium, 2023)
The Valley of Kashmir has a rich Folklore and folk literature is an integral part of Kashmiri Culture. Folkloristics maintains that the message conveyed through folklore may appear simple but it is intertwined with complexities. This paper attempts to study the folklore of Kashmir through an analysis of Kashmiri proverbs to uncover the simple/complex message transmitted through proverbs. The endeavour is to highlight how folklore is informed by Power relations and how the conception of Power interlaces the content, milieu and purpose of folklore. Michel Foucault traces the role of discourse underlying seemingly neutral context of speech, representation and knowledge. Along with Foucault’s concept of discourse, insights from feminist theory have also been employed to expose the discourse of patriarchy, religion and authority in Kashmiri folk literature. The study investigates the power structure inherent in the proverbs of Kashmir and attempts to unravel how discourse constructs unequal power relations. The attempt is to illustrate how power abuse is enacted, reproduced and legitimized.